Characteristics Nesting Ground of Turtle (Lepidochelys olivaceae) in Gampong Gelumpang Sulu Timur Dewantara Sub-district, North Aceh Regency - Muliani, Muliani; Erlangga, Erlangga; Mutia, Mutia; Ayuzar, Eva; Mahdaliana, Mahdaliana (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
One of the reptiles whose natural habitat is in the sea and has the ability to migrate very far is the turtle. Threats that endanger the turtle population, both directly and indirectly, come from natural sources and from human activities. The factors that influence turtle nesting ground were predators, sand grain size, substrate humidity, substrate temperature, beach width, coastal vegetation and beach slope. Humans as one of the predators of the availability of turtles in nature by taking turtle eggs. The aim of the study was to determine the nesting habitat characteristics of the Lekang turtle (Lepidochelys Olivaceae) in the coastal area of Gampong Geulumpang, East Sulu, Dewantara District, North Aceh Regency. This research was carried out in November 2021, which took place on the coast of the village of Gelumpang, East Sulu, Dewantara District, North Aceh Regency. In this study, observational data collection and biophysical measurements were set at 3 stations. Station 1 (Dusun Cot U Sibak), station 2 (Dusun Pasie Kuala), and station 3 (Dusun Teupin). The distance between stations in this study was Â± 2 km. Data analysis was carried out by weight body and scoring methods. Based on the results of data analysis from three observation stations at turtle nesting locations from several parameters such as beach slope is 4.5-9.3%, beach width is 10.20 -22 meters, the sand temperature is 29-32 0C, humidity is 21-28%, the size of the sand grains is 0.15322-0.31601 mm, while the coastal vegetation is 16.7-49.4%, it is concluded that the three observation stations are in the very suitable category for turtle nesting locations